STREETBALL IN PHYSICAL EDUCATION IN THE SCHOOLS (Fiep Bulletin - online, 2012)
This article is an initial part of a conclusion course work and deals with the inclusion of streetball or street basketball in the school environment, as the content of physical education as it presents itself as a relevant practice body surrounded by cultural meanings. Related to hip-hop movement, streetball appears in socio-sport scene widely publicized by the media, establishing an interesting relationship between the urban culture and the commodification of culture. Because streetball has already been incorporated spontaneously by students in public and private education, and has unique characteristics of a sports and cultural practice, has relevance to the study of a possible relationship with the formal education. Moreover, in this first step, it attempted to perform a theoretical survey of what streetball is, how it spread, what its socio-cultural aspects, which its sports aspects and its relationship with the “traditional” basketball. It was found that the inclusion of "new" in the teaching procedure is well received and, therefore, must be constant. The use of streetball, as well as new elements, provides a contextualized work with dance and rhythm in general (also physical education content), and other interdisciplinary areas such as history and sociology, the arts, the Portuguese and foreign, among other examples.
Keywords: streetball; urban culture; physical education.